2010
DOI: 10.1590/s1517-83822010000400025
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota associated with chronic osteomyelitis of the jaws

Abstract: Chronic osteomyelitis of maxilla and mandible is rare in industrialized countries and its occurrence in developing countries is associated with trauma and surgery, and its microbial etiology has not been studied thoroughly. The aim of this investigation was to evaluate the microbiota associated with osteomyelitis of mandible or maxilla from some Brazilian patients. After clinical and radiographic evaluation, samples of bone sequestra, purulent secretion, and biopsies of granulomatous tissues from twenty-two pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 27 publications
1
17
0
3
Order By: Relevance
“…Isolation of DNA from the surgical bone specimen or detection of E. coli and Enterococcus genes associated with specific virulence factors by polymerase chain reaction analysis may have been more effective in confirming whether those pathogens had been inoculated into the bone through the existing extraction wound. We speculate that the density (bacterial load) and/or virulence of enterococci, the ecological associations and/or interactions within the whole bacterial community present in the site of the bone infection, and other host‐related factors such as a possible temporary disturbance of the local immune defence may have been involved in the pathogenesis of this particular case. While it would have been ideal to investigate the immunocompetence of the patient by laboratory tests, this was not possible in our case; however, a thorough medical history did not reveal any suggestion of diabetes mellitus, HIV infection or other immunosuppression conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Isolation of DNA from the surgical bone specimen or detection of E. coli and Enterococcus genes associated with specific virulence factors by polymerase chain reaction analysis may have been more effective in confirming whether those pathogens had been inoculated into the bone through the existing extraction wound. We speculate that the density (bacterial load) and/or virulence of enterococci, the ecological associations and/or interactions within the whole bacterial community present in the site of the bone infection, and other host‐related factors such as a possible temporary disturbance of the local immune defence may have been involved in the pathogenesis of this particular case. While it would have been ideal to investigate the immunocompetence of the patient by laboratory tests, this was not possible in our case; however, a thorough medical history did not reveal any suggestion of diabetes mellitus, HIV infection or other immunosuppression conditions.…”
Section: Discussionmentioning
confidence: 93%
“…In ruminants, Tannerella forsythia has been identified in sheep (McCourtie et al 1989, Duncan et al 2003, Agostinho 2017, cattle (Borsanelli 2017), and goats (Campello 2017) with periodontitis. This microorganism has been frequently detected in human patients with periodontitis (Cortelli et al 2005, Foschi et al 2005, Feng & Weinberg 2006, Yoo et al 2007, Gaetti-Jardim et al 2010, Benrachadi et al 2012 and, initially, it was believed to be a relatively uncommon species found in the subgingival sulcus biofilm. Presently, it is known that its levels are strongly associated with increased depth of the periodontal pocket.…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction was performed in the material collected from the periodontal pocket and subgingival sulcus biofilm using a commercial kit (GenElute Mammalian Genomic DNA Miniprep Kit, Sigma). The search of Aggregatibacter actinomycetemcomitans, Campylobacter rectus, Eikenella corrodens, Enterococcus faecalis, Enterococcus faecium, Fusobacterium nucleatum, Porphyromonas gingivalis, Porphyromonas gulae, Prevotella intermedia, Prevotella nisgrescens, Tannerella forsythia and Treponema denticola was conducted with the use of specific primers (Ashimoto et al 1996, Gaetti-Jardim et al 2010, Kato et al 2011 (Table 1). The specificity of these primers has been demonstrated in the aforementioned literature and can be evaluated at the National Center for Biotechnology Information (NCBI) databases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A maioria das vezes, estas infecções são secundárias a processos cariosos, pericoronarite, doença periodontal e infecções endodônticas, podendo se espalhar pelos espaços fasciais da cavidade oral, crânio, pescoço e tórax, tornando-se uma ameaça à vida em curtos períodos de tempo (Hupp et al, 2014;Rajendra Santosh et al, 2017). O espalhamento também pode acontecer pela medula óssea, causando uma infecção dos ossos maxilares (Gaetti-Jardim et al, 2010;Lypka;Hammoudeh, 2011;Gaetti-Jardim et al, 2012).…”
Section: Introductionunclassified